Pembuatan seal tabung gas karet alam dengan filler pasir kuarsa sebagai pengganti karbon hitam - Suharman, Suharman; Harun, M. (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
This research aimed to make natural rubber-based gas cylinder seals with quartz sand as the filler to replace carbon black. The experiments consisted of the use of 10 phr, 20 phr, 30 phr, 40 phr, and 50 phr of quartz sand. The gas cylinder seals produced underwent a test according to the Indonesian National Standard (SNI) 7655:2010. The test generated the following results: the value of hardness ranged from 51Â±6 to 60Â±5 Shore A, the value of tensile strength ranged from 67 to 72 kg/cm2, the value of elongation at break ranged from 414 to 457%, the value of the compression set ranged from 25 to 61%, after aging, and ozone resistance with no cracks. Natural rubber-based gas cylinder seals with quartz sand as the filler to replace carbon black met the requirements specified by SNI 7655:2010 in terms of the criteria of hardness, elongation at break, after aging and ozone resistance.Keywords: quartz sand, carbon black, gas cylinder seal.Â